Customs policy as a tool to stimulate exports under martial law - Andrii Dziubynskyi; Olena Pakholiuk; Oksana Dziubynska; Oleg Shehynskyi; Volodymyr Shehynskyi (Economic Forum, 2025)
The purpose of the article was to study the specifics of the functioning of Ukraine's customs policy under martial law, with a special emphasis on the mechanisms for stimulating export activities and ensuring the efficiency of the state's foreign economic processes. The methods of analysis, synthesis, comparison, generalisation of data and logical conclusion of the analysis were used for the study. An integrated approach allowed for a systematic study of the multifaceted nature of customs policy, which included interrelated components. The use of the abstract and logical method contributed to the formulation of the key areas of modernisation of Ukraine's customs policy in the context of martial law and European integration. The paper examined the peculiarities of Ukraine's customs policy under martial law, analysed the indicators of foreign trade at the beginning of the war and the activities of the State Customs Service. The key objectives of the customs policy were identified: export development, protection of the internal market and support for the competitiveness of Ukrainian goods. For this purpose, customs tariffs with protective and incentive functions were applied in accordance with economic needs and international obligations. Exports declined, particularly in 2022, but stabilised in 2024. The index of physical exports increased, indicating that production processes improved. The agricultural sector suffered the largest losses. At the same time, the EU and Canada's decision to temporarily exempt Ukrainian goods from duties contributed to trade liberalisation. Military actions and the blockade of ports changed logistics: rail transport replaced sea transportation, which complicatedthe work of customs due to the increase in the volume of goods flows. It was proposed simplified approaches to export procedures that can stimulate foreign economic activity. The economic effect of the proposed changes was estimated as a basis for new strategic objectives in the field of foreign trade. The practical value of the work is to provide adaptive solutions to the conditions of uncertainty and chaos arising from the martial law in Ukraine, as well as to improve the procedures and processes of foreign economic activity
Keywords: 330; state economic policy; customs; export activity; foreign economic activity; martial rule